Human–machine shared control for vehicle lane keeping systems: a Lyapunov‐based approach. Issue 1 (12th October 2018) - Sentouh, Chouki; Nguyen, Anh‐Tu; Rath, Jagat Jyoti; Floris, Jérôme; Popieul, Jean‐Christophe
Abstract : In this work, a human‐centred steering assist controller based on dynamic allocation of control authority between driver and automatic e‐copilot has been proposed for lane keeping systems. Cooperative control between driver and steering assist controller is addressed taking into consideration human driving behaviour. The vehicle steering controller for lane keeping is designed using a driver model for representation of the conflict between the driver and the controller. The steering controller is designed employing the integrated driver‐vehicle model using Takagi–Sugeno control technique coupled with Lyapunov stability tools. The proposed design is robust to longitudinal speed variations and involves a trade‐off between the lane following performance and ratio of negative system interference. The proposed approach was implemented on dynamic vehicle simulator SHERPA and the results presented in this study demonstrate the effectiveness of the proposed structure for cooperative control action between human driver and the steering assistance system. Based on indices such as energies spent by driver, driver satisfaction level and contradiction level between driver and autonomous controller the proposed optimal approach shows 93.48% and 89.30% reductions in expended driver energy and contradiction levels. Further, the satisfaction level of driver increased by 67.80% while performing a lane change manoeuvre.